2022
DOI: 10.48550/arxiv.2203.07675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparing for low surface brightness science with the Vera C. Rubin Observatory: characterisation of tidal features from mock images

G. Martin,
A. E. Bazkiaei,
M. Spavone
et al.

Abstract: Tidal features in the outskirts of galaxies yield unique information about their past interactions and are a key prediction of the hierarchical structure formation paradigm. The Vera C. Rubin Observatory is poised to deliver deep observations for potentially of millions of objects with visible tidal features, but the inference of galaxy interaction histories from such features is not straightforward. Utilising automated techniques and human visual classification in conjunction with realistic mock images produc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 188 publications
(251 reference statements)
0
1
0
Order By: Relevance
“…These studies have also shown that the stellar halos are expected to be populated primarily by the stellar debris of these mergers, which may take the form of coherent tidal features (Martínez-Delgado et al 2010;Vera-Casanova et al 2021;Martin et al 2022) or substruc-tures thoroughly spatially-mixed with the halo but which could be disentangled in phase space (e.g. .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also shown that the stellar halos are expected to be populated primarily by the stellar debris of these mergers, which may take the form of coherent tidal features (Martínez-Delgado et al 2010;Vera-Casanova et al 2021;Martin et al 2022) or substruc-tures thoroughly spatially-mixed with the halo but which could be disentangled in phase space (e.g. .…”
Section: Introductionmentioning
confidence: 99%